[LETTER FROM THE TEAMSTERS UNION REGARDING COLLECTIVE BARGAINING FOR THE RIGHT TO SMOKE] (Tufts Archival Research Center, 2007)
Letter from the Teamsters Union regarding smoking in the workplace. Praises the collective bargaining process as one that is sacred in guaranteeing the rights of workers. Expresses concern that people working alone in the trucking or package delivery industry are not being properly considered in workplace smoking restrictions. Requests the workplace smoking issue be handled via collective bargaining.